Dynamic Air Traffic Control Wake Vortex Safety and Capacity System - Peter Choroba (Communications - Scientific letters of the University of Zilina, 2004)
International regulations require aircraft to be separated in approach phase of flight by up to six nautical miles (11.12 km) due to the potential hazard caused by the swirling air left in their wakes. This ‘wake vortex’ is now the subject of intense worldwide research to understand the nature of the phenomenon and find ways of making air travel safer while reducing congestion around airports. “With the world airline fleet expected to double in size over the next 15 years and the giant A380 entering service in 2005, solutions to the wake-vortex problem cannot come too soon for the aerospace industry and therefore there is a strong need for developing a dynamic air traffic control wake vortex safety and capacity system.” [1] This paper describes the concept of integrated transportation system regarding the current state-of-the-art technologies.